2008
DOI: 10.1111/j.1365-2524.2007.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Confidentiality smokescreens’ and carers for people with mental health problems: the perspectives of professionals

Abstract: This paper reports on some of the findings from a collaborative study funded by the Big Lottery and led by Crossroads Caring for Carers about carers for people with mental health problems. The protection and use of information in mental health are firmly rooted in ethics and professional codes, law and policy, as well as values and professional practice. While government initiatives have attempted to augment the role and rights of carers, policy guidance involving information sharing between professionals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 14 publications
2
89
0
5
Order By: Relevance
“…Carers are recognised as adding to the quality of care for older people as they bring a holistic knowledge of the person (sometimes over a life time) that positively contributes to care planning and maintaining the person's well-being (Gray et al, 2008;Milligan, 2006). In our study, carers highlighted the value of the relationship with the worker and the older person as well as the importance of social contacts for the older person.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Carers are recognised as adding to the quality of care for older people as they bring a holistic knowledge of the person (sometimes over a life time) that positively contributes to care planning and maintaining the person's well-being (Gray et al, 2008;Milligan, 2006). In our study, carers highlighted the value of the relationship with the worker and the older person as well as the importance of social contacts for the older person.…”
Section: Discussionmentioning
confidence: 76%
“…Interviews highlighted that there was no overarching professional care coordinator that bridged all sectors (health, aged and social care) and subsequently carers found they were often the primary navigator across services. Commonwealth of Australia, 2009), mental health workers interpretation of confidentiality provisions has been found to create 'confidentialitysmokescreens' that limits information sharing (Gray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones (2004) further argues that relatives of someone with a severe mental illness experience complex emotions of guilt and loss. When not involved by professionals, carers describe feelings of anxiety, depression, isolation, fear, anger and resentment towards the person with mental health problems (Wooff et al 2003, Wynaden & Orb 2005, Gray et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Rapaport (2006), in a large survey of service users, carers and professionals, found that each group had differing views about what information should be shared. Professionals hide behind what Gray et al (2008) have termed 'confi dentiality smokescreens' because of the unsolved moral and ethical dilemma of the service user's need for privacy and the carer's need for information. There is no clear guidance about information sharing despite policies and guidance about carers' rights and roles.…”
Section: International Journalmentioning
confidence: 99%